2015
DOI: 10.3109/1354750x.2015.1068851
|View full text |Cite
|
Sign up to set email alerts
|

Individual variability of high-sensitivity cardiac troponin levels after aerobic exercise is not mediated by exercise mode

Abstract: Individual variability of high-sensitivity cardiac troponin levels after aerobic exercise is not mediated by exercise mode http://researchonline.ljmu.ac.uk/3170/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…This study confirms that the exercise-induced release of cTn and NT-proBNP is not exclusive to an ultra-endurance effort in adult athletes. 5,6,23,24 There is some evidence to suggest that cTn release during prolonged exercise is positively associated with exercise intensity. 25,26 Thus, the high intensity shown by our swimmers could explain the release of hs-cTnT.…”
Section: Hs-ctnt and Nt-probnp Release Postexercisementioning
confidence: 99%
“…This study confirms that the exercise-induced release of cTn and NT-proBNP is not exclusive to an ultra-endurance effort in adult athletes. 5,6,23,24 There is some evidence to suggest that cTn release during prolonged exercise is positively associated with exercise intensity. 25,26 Thus, the high intensity shown by our swimmers could explain the release of hs-cTnT.…”
Section: Hs-ctnt and Nt-probnp Release Postexercisementioning
confidence: 99%
“…Further determination of factors mediating this heterogeneity was constrained by our relatively small and homogeneous cohort. Of note, addressing a principal limitation of other studies 16,32,33,35 that typically focused on single factors, Eijsvogels et al assessed the influence of multiple parameters on post-exercise cTnI levels in a large and heterogeneous cohort and noted a large portion (>90%) of the post-exercise cTnI levels cannot be explained. 36 Therefore, one may suggest that cTn increases seem to be random and be irrespective of subject and exercise characteristics.…”
Section: Individual Variability In Ctnt Response To Acute Interval mentioning
confidence: 99%
“…An interesting observation into the nature of hscTn elevations stems from cardiac biomarker studies in young, healthy adults during exercise, where a substantial number of athletes develop significant post-exercise hscTn elevation >300%. 8,22 The origin is not well understood, but some data suggest that the aetiology for such elevations is the right ventricle. 23,24 Typically, hscTn elevations after myocardial injury are more sustained (>12 h), whereas exercise-induced hscTn elevation in athletes without cardiac symptoms can be short lived (<12 h), 25 although studies are lacking that measure the duration until hscTn values return to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study in healthy triathletes found a >300% increase of cTn concentrations after 1 h of high-intensity exercise. 8 A study involving healthy volunteers showed that a brief dobutamine infusion causes an increase in high-sensitivity cardiac troponin T (hscTnT). 9 Likewise, rapid atrial pacing leads to a significant increase in hscTnT, both in patients with or without significant coronary-artery disease.…”
mentioning
confidence: 99%